SYNTHESIS AND CHARACTERIZATION OF COBALT BIMETALLIC NANOCATALYSTS ON ALUMINA - Ali, Sardar (2009)
The present work deals with the synthesis of cobalt bimetallic Co/Mo nanocatalysts supported on alumina. The nanocatalysts were prepared by wet impregnation and co-precipitation method. The samples were characterized in terms of reducibility, dispersion and particle size using Temperature Programmed Reduction (TPR), X-ray diffraction analysis (XRD), Transmission Electron Microscopy (TEM) and BET-surface area analysis. H2-TPR analysis of Co/Al2O3 indicated three temperature regions at 380◦C (low temperature), 680◦C (medium temperature) and 900 ◦C (high temperature). The incorporation of molybdenum into cobalt nanocatalysts shifted the reduction temperatures towards higher temperature but the percentage of species being reduced at low temperature increased. It was found that incorporation of molybdenum into cobalt nanocatalysts increased the species reducibility due to increase in the particle size as evident by the TEM result. For 5%wt Co the average particle size was 14 nm while for 5%wt Co/Mo nanocatalysts the average particle size was found to be 25 nm. XRD showed that crystallinity of bimetallic nanocatalysts was lower than that of the monometallic nanocatalysts.The precipitation synthesis approach was found to be better method than the impregnation method for the preparation of cobalt bimetallic nanoparticles supported on alumina.